The evolving landscape of learning technology - Gráinne Conole (Association for Learning Technology, 2002)
This paper provides an overview of the current and emerging issues in learning technology research, concentrating on structural issues such as infrastructure, policy and organizational context. It updates the vision of technology outlined by Squires' (1999) concept of peripatetic electronic teachers (PETs) where Information and Communication Technologies (ICT) provide an enabling medium to allow teachers to act as freelance agents in a virtual world and reflects to what extent this vision has been realized The paper begins with a survey of some of the key areas of ICT development and provides a contextualizing framework for the area in terms of external agendas and policy drivers. It then focuses upon learning technology developments which have occurred in the last five years in the UK and offers a number of alternative taxonomies to describe this. The paper concludes with a discussion of the issues which arise from this work.